Cubes, cones, cylinders & spheres - Hoban, Tana. (New York : Greenwillow Books, 2000)
Photographs of all kinds of familiar objects depict a variety of shapes, including cubes, cones, and spheres.
NP
Keywords: Geometry -- Pictorial works -- Juvenile literature; Shape; Illustrated works; Literature